Maternal Obesity Is an Independent Risk Factor for Intensive Care Unit Admission during Delivery Hospitalization - Masters, Heather R.; Housley, Emily; Van Hook, James W.; DeFranco, Emily (American Journal of Perinatology, 2018)
Objective We aim to quantify the impact of obesity on maternal intensive care unit (ICU) admission.Materials and Methods This is a population-based, retrospective cohort study of Ohio live births from 2006 to 2012. The primary outcome was maternal ICU admission. The primary exposure was maternal body mass index (BMI). Relative risk (RR) of ICU admission was calculated by BMI category. Multivariate logistic regression quantified the risk of obesity on ICU admission after adjustment for coexisting factors.Results This study includes 999,437 births, with peripartum maternal ICU admission rate of 1.10 per 1,000. ICU admission rate for BMI 30 to 39.9 kg/m2 was 1.24 per 1,000, RR: 1.20 (95% confidence interval [CI]: 1.07, 1.35); BMI 40 to 49.9 kg/m2 had ICU admission rate of 1.80 per 1,000, RR: 1.73 (95% CI: 1.38, 2.17); and BMI ≥ 50 kg/m2 had ICU admission rate of 2.98 per 1,000, RR: 1.73 (95% CI: 1.77, 4.68). After adjustment, these increases persisted in women with BMI 40 to 49.9 kg/m2 with adjusted relative risk (adjRR) of 1.37 (95% CI: 1.05, 1.78) and in women with BMI ≥ 50 kg/m2, adjRR: 1.69 (95% CI: 1.01, 2.83).Conclusion Obesity is a risk factor for maternal ICU admission. Risk increases with BMI. After adjustment, BMI ≥ 40 kg/m2 is an independent risk factor for ICU admission.
Keywords: ICU admission; maternal obesity; severe maternal morbidity